Only Light Physical Activity is Associated With Good Perceived Health and Fitness in Terms of Both Absolute and Relative Intensity (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Physical activity (PA) is associated with perceived health and fitness, but associations of broader concept of physical behaviour and relative intensities of PA have been studied less. This study analysed how daily physical behaviour – in terms of lying, reclining, sitting, and standing, both absolute and relative individual intensities of PA, number of steps, and peak 1-min metabolic equivalents (MET) – is associated with perceived health and fitness.Methods: The study is based on combined data from two cross-sectional population-based FINFIT studies that measured physical behaviour by a triaxial hip-worn accelerometer (UKK RM42) among 20–69-year-old adults. Lying, reclining, sitting, and standing during waking hours were analysed by the APE-algorithm and PA by the MAD-algorithm. The range for absolute light PA (LPA) was 1.5–2.9 METs. The cut point for absolute moderate PA (MPA) was ≥3 METs and for vigorous PA (VPA) ≥6 METs. The cut point for relative LPA was